HIKMAH KEISTIQOMAHAN IBLIS DALAM KONSPIRASI JAHAT MENGGELINCIRKAN UMAT MANUSIA KE JURANG NERAKA - El Syam, Robingun Suyud; Muntaqo, Lutfan (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2024)
This article attempts to uncover the wisdom of Satan's steadfastness in his evil conspiracy to plunge humanity into the abyss of hell, a practice previously undiscovered. This paper is a qualitative literature review using inductive analysis. The results show that the presence of evil entities does not mean there is nothing to learn from them, including learning to be steadfast like Satan. Steadfastness allows humans to survive alongside various other types of humans from the beginning of human creation to the present modern era. This steadfastness is crucial to maintain as a supporter of carrying out and spreading goodness so that it continues to thrive. The difference in steadfastness between a wise person and Satan lies in the values they seek to embody, namely good and evil. If Satan is more adaptable and flexible in pursuing evil, then goodness will have an increasingly difficult time accompanying the progress and development of human civilization on earth. Research Implications: The author deliberately invites readers not to comment on the results, but emphasizes the importance of taking advantage of them objectively, rather than subjectively. This research provides recommendations for further research in more specific areas.